Impact of Antibiotic Gut Exposure on the Temporal Changes in Microbiome Diversity - Charles Burdet; Thu Thuy Nguyen; Xavier Duval; Stéphanie Ferreira; Antoine Andremont; Jérémie Guedj; France Mentré; B. Ait-Ilalne; Loubna Alavoine; Xavier Duval; J. L. Ecobichon; Emila Ilic-Habensus; et al. (2019)
Although the global deleterious impact of antibiotics on the intestinal microbiota is well known, temporal changes in microbial diversity during and after an antibiotic treatment are still poorly characterized. We used plasma and fecal samples collected frequently during treatment and up to one month after from 22 healthy volunteers assigned to a 5-day treatment by moxifloxacin ( n = 14) or no intervention ( n = 8).